Factors influencing the transition to renewable energy in small- to mid-sized American communities - Hanan Wehbi; Nathan Kemper (Energy, Sustainability and Society)
Abstract Background The transition to renewable energy is essential for addressing climate change and fostering sustainable communities. This involves planning and determining where, when, and how to deploy renewable energy technologies. This requires supportive policies and regulations to accommodate renewable energy sources and manage impact, as well as engagement with local communities and stakeholders to secure their support and participation in the transition process. Methods This study evaluates the impact of governance at various levels—community, county, and state—on renewable energy adoption in 87 small- to mid-sized U.S. communities with populations below 100,000. Using a multi-faceted analytical approach, this research reviews comprehensive climate action and sustainable plans to identify key drivers of renewable energy transitions. This study explores whether local government plans and multi-level governance efforts enhance renewable energy adoption in these communities. By examining the integrated policy approach, this research explores the interplay between governance levels and their collective impact on renewable energy consumption through regression and comprehensive content analysis. Results Content analysis of 134 reviewed community, county, and state plans revealed that local governments adopt renewable energy targets in their local plans less frequently than state and county governments do. Among the 87 communities studied, 63% implemented limited renewable energy consumption, with percentages ranging from 5 to 30%. In contrast, only four communities (5%) achieved full renewable energy dominance with 100% renewable energy consumption. Regression analysis identified four significant factors influencing renewable energy consumption percentages: building energy efficiency measures at the community level, sustainable land use promotion at the county level, renewable energy targets, and sustainable land use frameworks at the state level. Conclusions This study underscores the significance of a multi-level governance approach in facilitating local energy transitions, noting that successful implementation relies on efforts from local governments. It stresses the need for integrated policy frameworks that synchronize state, county, and local actions to develop supportive policies and regulations for effective land use planning, energy efficiency measures, and community engagement to achieve renewable energy targets more effectively.